U lành cơ trơn nguyên phát ở phổi: báo cáo hai ca lâm sàng - Dũng, Nguyễn Huy; Lân, Nguyễn Hữu; Hiền, Nguyễn Thanh; Phùng, Nguyễn Trần; Lam, Nguyễn Sơn; Dũng, Lê Tiến; Vũ, Nguyễn Thế; Thiết, Trương Thanh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.